Depression and anxiety in mothers of home ventilated children before and during COVID-19 pandemic - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background: Due to advances in technology, home ventilation in children has increased in recent years. The provision of proper care for a home-ventilated (HV) child can have a strong impact on the lifestyle of caregivers. The aim of this study was to evaluate the depression and anxiety levels of the mothers of HV children during the current COVID-19 pandemic and compare them to those of mothers of healthy peers. Methods: This cross-sectional study was conducted on HV children (n = 21) and a control group of healthy peers (n = 32) by means of a questionnaire completed by the mothers of the children of both groups. Psychometric scales, such as the Beck Depression Inventory (BDI), the State-Trait Anxiety Inventory-State (STAI-S), and the State-Trait Anxiety Inventory-Trait (STAI-T), were used to assess participants. Results: During the pandemic signs of depression were present in 8 (38.1%) of the case group and 8 (25%) of the healthy control group. Comparison of the BDI scores from before and during the pandemic showed no difference between mothers of the HV children (p = .09). Scores for BDI and STAI-T were higher in the case group than in the control group, whereas there was no significant difference in STAI-S scores. Conclusion: Depression and anxiety levels of mothers of HV children were found to be higher during the COVID-19 pandemic. Economic, medical, and social support resources are needed to reduce levels of depression and anxiety and help mothers of those children dependent on technology.
Keywords: caregiver; mental health; pandemic; QUALITY-OF-LIFE; SOCIAL SUPPORT; TECHNOLOGY; CAREGIVERS; FAMILIES; EXPERIENCE; DISEASE; HEALTH; IMPACT